A perennial philosophy of nature - Carlson, Brian G. (Proceedings of the American Catholic Philosophical Association, 2021)
Presidential address.The significance of hylomorphism /Jean De Groot --Aquinas medalist's address.Aquinas the Avicennian: Prologue to the Commentary on Aristotle's metaphysics /R.E. Houser --Plenary sessions.Empiricism and natural philosophy /James Mattingly --Nature and ethics /Joseph W. Koterski, S. J. --A perennial theology of nature /Anselm Ramelow, O.P. --Session 1: Natural place and rest.A defense of natural place in a contemporary scientific context /Thomas McLaughlin --Aristotle on activity as a variety of rest /Christopher Frey --Session 2: Aristotle's cosmology today.Perennial symmetry agruments: Aristotle's heavenly cosmology and Noether's first theorem /Ryan Michael Miller --Is Aristotelian-Thomistic natural philosophy still relevant to cosmology? /John G. Brungardt --Session 3: Philosophy of nature, metaphysics, and theology.Theistic moral realism, evolutionary debunking arguments, and a Catholic philosophy of nature /Michael Rauschenbach --Relation is not a category: a sketch of relation as a transcendental /Christopher V. Mirus --Session 4: Aristotelian natural philosophy.Albertus Magnus and Thomas Aquinas on what is "better-known" in natural science /John H. Boyer and Daniel C. Wagner --Generation and homonymy in Aristotle's Generation of animals /Ignacio de Ribera-Martin --Session 5: Virtue.The nature of virtue ethics /Allison Postell --Is piety a natural virtue? /M.T. Lu --Session 6: Esse in St. Thomas Aquinas."In as many ways as something is predicated ... in that many mays is something signified to be" /Elliot Polsky --Divine esse without ontological significance: Jean-Luc Marion's challenge to Aquinas /Jameson Cockerell --Session 7: Aristotle and modern science.Substantial form in modern physics and the other sciences: and a new picture of the cosmos /Timothy Kearns --Session 8: A perennial philosophy of nature.Is philosophy of nature irrelevant? /Daniel D. De Haan --A defense of the distinction between plants and animals /Marie I. George --ACPA reports and minutes.